2019
DOI: 10.1080/09540121.2019.1640842
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of care for HIV-seroconverters in rural Tanzania: a longitudinal study

Abstract: We examined the HIV care cascade in a community-based cohort study in Kisesa, Magu, Tanzania. We analyzed the proportion achieving each stage of the cascade -Seroconversion, Awareness of HIV status, Enrollment in Care and Antiretroviral therapy (ART) initiation-and estimated the median and interquartile range for the time for progression to the next stage. Modified Poisson regression was used to estimate prevalence risk ratios for enrollment in care and initiation of ART.From 2006 to 2017, 175 HIV-seroconverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four [ 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] studies reported on people diagnosed with HIV and aware of their status, with 19 providing definitions for the denominator and numerator. Ten were cross‐sectional, 10 longitudinal and 4 included longitudinal and cross‐sectional components (mixed design).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations